An economic analysis of salmonella detection in fresh produce, poultry, and eggs using whole genome sequencing technology in Canada. (February 2019) - Jain, Sonali; Mukhopadhyay, Kakali; Thomassin, Paul J.
Abstract: The study estimates the annual costs of nontyphoidal Salmonellosis (referred to as Salmonellosis from hereon) from fresh produce, poultry and eggs in Canada. It also estimates the economic benefits from introduction of Whole Genome Sequencing (WGS) in detection of Salmonellosis clusters and outbreaks. Monetary and non-monetary costs from Salmonellosis are estimated. Monetary costs are divided into direct healthcare, indirect, federal and producer costs. Probability models are used to account for uncertainty in the cost-of-illness estimates. Two types of non-monetary costs have been estimated: Disability-adjusted Live Years and Quality-adjusted Life Years. These estimates are then used to calculate the economic impact of WGS on detection of Salmonellosis. The estimated incidence of illnesses is 47, 082 annually, which represents a cost of $287.78 million (total cases) and $166.28 million (reported cases) from the traditional technology. The total net benefit from introduction of WGS is estimated to range from $5.21 million-$90.25 million. All monetary values are in CAD unless stated otherwise. WGS will help in reducing the economic burden from Salmonellosis. These estimates help will aid policy related decision making. Graphical abstract: Unlabelled Image Highlights: Salmonellosis in Canada from fresh produce, poultry and eggs are 47, 082 annually. PFGE cost is $287 million for Salmonellosis in Canada. DALY and QALY is estimated to be 529 and 289 respectively. The net benefits of WGS ranging from $5–$90 million.